(untitled) (Ameghiniana, 2014)
In 1949 Schaeffer described several anuran taxa based on remains from Deseadan beds of the western part of the meseta Canquel in central Patagonia. Among those taxa is the extinct neobatrachian Neoprocoela edentata Schaeffer, the evolutionary relationships of which are still controversial. It was suggested that this species is related to the Bufo calamita Laurenti species group, which has a Palearctic distribution at present. Subsequently, it was claimed that additional material collected from the same beds and locality confirmed the presence of the B. calamita group in Patagonia. The specimen on which this latter statement apparently was based was prepared and is described herein. Comparisons of the preserved elements neither support referral to Neoprocoela, nor their bufonid affinities; instead, the squamosals, vertebral column, humeri, and ilia resemble those of telmatobine "leptodactylids".